Correlates of pregnant women's gestational weight gain knowledge. (June 2017) - Willcox, Jane Catherine; Ball, Kylie; Campbell, Karen Jane; Crawford, David Andrew; Wilkinson, Shelley Ann
Abstract: Objective: to investigate correlates of pregnant women's gestational weight gain (GWG) knowledge commensurate with GWG guidelines. Design: cross sectional quantitative study. Setting: an Australian tertiary level maternity hospital. Participants: pregnant women ( n =1032) following their first antenatal visit. Measurements: survey to assess GWG knowledge and a range of potential correlates of knowledge including socio-economic characteristics, pregnancy characteristics (parity, gestation, pre-pregnancy BMI) and GWG information procurement and GWG attitudinal variables. Findings: participants ( n =366; 35.4% response) averaged 32.5 years of age with 33% speaking a language other than English. One third of women reported GWG knowledge consistent with guidelines. Women overweight prior to pregnancy were less likely to underestimate appropriate GWG (RRR 0.23, 95% CI=0.09–0.59). Conversely, women in the overweight (RRR 8.80, 95% CI=4.02–19.25) and obese (RRR 19.62, 95% CI=8.03–48.00) categories were more likely to overestimate GWG recommendations, while tertiary educated women were less likely to overestimate GWG (RRR 0.28, 95% CI=0.10–0.79). No associations were found between GWG knowledge and pregnancy, GWG information source or attitudinal variables. Conclusions and implications for practice: the findings highlight women's lack of GWG knowledge and the role of pre-pregnancy body mass index and women's education as correlates of GWG knowledge. Women susceptible to poor GWG knowledge should be a priority target for individual and community-based education. Highlights: One third of women reported gestational weight gain knowledge consistent with guidelines. Women overweight prior to pregnancy were less likely to underestimate appropriate gestational weight gain. Tertiary educated women were less likely, and overweight women were more likely, to overestimate gestational weight gain. No associations were found between weight gain knowledge and pregnancy, information procurement or attitudinal variables.